Deposition of titanium based coatings by reactive detonation spraying; Koroze a ochrana materialu; Vol. 62, iss. 1 - Panin S. V. Sergey Viktorovich; Vlasov I. V. Ilya Viktorovich; Dudina D. V. Dina Vladimirovna; Stankevich R. V. Roman Vladimirovich; Marushchak P. O. Pavel Orestovich; Batraev I. S. Igor Sergeevich; Landova M. Marina (2018, 2018)
Title screen